Kepailitan Perusahaan Asuransi antara Kepastian Hukum dan Perlindungan Konsumen - Maprilia Janur Putri, Ananda (Zaaken: Journal of Civil and Business Law, 2025)
This study aims to analyze the bankruptcy of insurance companies from juridical, philosophical, and sociological perspectives within the framework of Indonesian legislation. The main issue addressed is the legal vacuum in filing a Suspension of Debt Payment Obligations (PKPU) against insurance companies, in which authority is exclusively held by the Financial Services Authority (OJK), while policyholders face limited legal access. This research employs a normative juridical method with statutory, case, and conceptual approaches. The findings reveal that, juridically, restricting the authority to file PKPU solely to OJK creates legal uncertainty for policyholders. Philosophically, the application of John Rawls’ theory of justice demonstrates an imbalance between safeguarding the stability of the insurance industry and protecting consumer rights. Sociologically, such restrictions have undermined public trust in the insurance sector and reduced the effectiveness of consumer protection. These findings emphasize the need to strengthen bankruptcy regulations for insurance companies in order to ensure legal certainty while simultaneously protecting policyholders as vulnerable parties.